Exchange Method Using Acid‐Solvent Synergy for Metal–Organic Framework Synthesis (EASY‐MOFs) Based on a Typical Pillar‐Layered Parent Structure. Issue 10 (10th March 2016) - He, Yingdian; Shang, Jin; Gu, Qinfen; Zhao, Qinghu; Xie, Ke; Li, Gang; Singh, Ranjeet; Xiao, Penny; Webley, Paul A.
Abstract: We report an advanced synthesis strategy, termed "exchange method using acid‐solvent synergy for metal–organic framework synthesis" (EASY‐MOFs), which can generally be applied to pillar‐layered MOFs to generate new structures. Superior to de novo synthesis, EASY‐MOFs provides an alternative synthesis route with advantages of high product purity, structural versatility and controllability. In addition, high product yield is possible without the need for tedious optimization of the synthetic conditions, which is often the case for de novo synthesis. More importantly, novel structures that are not obtainable by direct synthesis or conventional ligand‐exchange strategies can be achieved by EASY‐MOFs. Based on our experimental observations, we attribute the unique advantages of EASY‐MOFs to the nucleation rate control during the disassembly–exchange–reassembly process and the seeding effect of the parent crystals promoted by the acid. Abstract : The exchange method using acid‐solvent synergy for metal‐organic framework synthesis (EASY‐MOFs) demonstrates considerable advantages in terms of product purity, structural versatility and controllability.